On Theft and Thunder: Genderfluid Comedy in Þrymskviða - Sommer, Anna Olivia (Meliora, 2026)
In The Elder Edda’s predominantly tragic collection of Old Norse poems, “Þrymskviða” (“The Lay of Thrym”) stands apart as a comedy centering on a gender-bending taboo: Thor crossdressing as the goddess Freya to retrieve his stolen hammer, Mjölnir. This paper investigates how the poem maintains its structural logic of comedy—as the inverse of tragedy—despite Thor risking accusations of ergi (unmanliness) and níð (social dishonor) by violating the 12th-century Grágás-laws that explicitly forbade crossdressing. Through analysis of both Old Norse and translated versions, I argue that the narrative carefully distinguishes between aesthetic transformation (crossdressing) and total transformation (shapeshifting). Thor’s bridal disguise remains superficial, with the narrative maintaining masculine pronouns and emphasizing the discrepancy between his feminine appearance and masculine behavior. Further, I examine how divine precedents, particularly Odin’s practice of seiðr (traditionally feminine magic) and Loki’s gender fluidity, establish that gods operate beyond human legal constraints. The poem’s resolution through extreme violence becomes essential to the comedic mode, transforming Mjölnir from a symbol of union back into an instrument of masculine dominance. Ultimately, “Þrymskviða” offers what the rest of The Elder Edda rarely does: hope that cosmic order can be restored, and that the anthropomorphic gods, as well as the people worshipping them, can retain agency over their fate.